PENGGUNAAN MEDIA PUZZLE HURUF DALAM MENINGKATKAN LITERASI MEMBACA AWAL ANAK DI SEKOLAH DASAR - Husnul Hidayatun Nisa; Pratiwi Dwi Warih Sitaresmi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the effectiveness of using letter puzzle media to improve early reading literacy skills among first-grade elementary school students in a home-based tutoring environment. A descriptive qualitative approach was employed, with data collected through observation, in-depth interviews, and documentation. The research subjects consisted of 10 students, one main tutor, and several parents. The findings indicate that the use of letter puzzles significantly enhanced students’ ability to recognize letters, form syllables, and read simple words. Students demonstrated high enthusiasm, active engagement, and increased self-confidence during the learning process. The tutor played a key role as a facilitator in creating a supportive learning environment, while the letter puzzle served as a multisensory stimulus that facilitated comprehension. These findings align with constructivist learning theory and Vygotsky's zone of proximal development, emphasizing active learning through appropriate media support. This study recommends the use of creative concrete media in early reading instruction, both in formal and non-formal educational settings.